A Fluidic Muscle által kifejtett erő közelítésének vizsgálata MS Excel környezetben - Sárosi, József; Fabulya, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The newest and most promising type of pneumatic actuators is the pneumatic artificial muscle (PAM). Different designs have been developed, but the McKibben muscle is the most popular and is made commercially available by different companies (e. g. Fluidic Muscle manufactured by Festo Company and Shadow Air Muscle manufactured by Shadow Robot Company). Pneumatic artificial muscles have a wide range of use in industrial and medical fields. There are a lot of advantages of these muscles like the high strength, good power-weight ratio, low price, little maintenance needed, great compliance, compactness, inherent safety and usage in rough environments. The main disadvantage is that their dynamic behaviour is highly nonlinear. The most often mentioned characteristic of PAMs is the force as a function of pressure and contraction. In this paper the newest function approximations for the force generated by Fluidic Muscles are investigated in MS Excel.